REDESIGN OF PANTI WILASA CITARUM CLASS C GENERAL HOSPITAL IN SEMARANG CITY - Rosidatun Khilmiyah; Eko Budi Santoso; Andi Purnomo (Universitas Negeri Semarang, 2025)
The Inpatient Installation (IRI) is one of the essential basic medical services that must be provided in Class C General Hospitals, in accordance with the policies of the Ministry of Health of the Republic of Indonesia. However, many inpatient facilities still do not meet the applicable regulations, including the Minister of Health’s Regulation, Standard Inpatient Care Policies, and local regulations. Redesign of Panti Wilasa Citarum Class C General Hospital in Semarang City, addresses the urgency for spatial and functional improvements aligned with national healthcare standards. This project focuses on revamping the Inpatient Department (IRI), which currently suffers from over-congested building masses, inadequate green space, and poor natural lighting. The redesign adopts a Contextual Architecture approach to integrate environmental responsiveness, regulation compliance, and user-centric healing environments. Methodologies include spatial and regulation analysis, site observation, and benchmarking of successful hospital projects. The outcome is a masterplan and architectural design that enhances circulation efficiency, supports health services, and introduces passive design strategies for thermal comfort. The project not only improves the spatial layout of the inpatient facility but also contributes to better healthcare quality and aligns with local urban planning regulations.